2020
DOI: 10.3389/fcell.2020.582715
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Protects Porcine Oocytes From Microcystin-LR Toxicity During Maturation

Abstract: Microcystin-leucine arginine (MC-LR) is the most toxic cyanotoxin found in water bodies. Microcystins are produced as secondary products of cyanobacteria metabolism. They have a stable structure, and can bioaccumulate in living organisms. Humans and livestock who drink fresh water containing MC-LR can be poisoned. However, few studies have reported the effects of MC-LR exposure on livestock or human reproduction. In this study, we used porcine oocytes as a model to explore the effects of MC-LR on oocyte matura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…The epigenetic alterations induced by advanced maternal aging, mitochondrial dysfunctions, abnormal nutrition supply and abnormal expression levels of hormones trigger seriously meiotic defects of mammalian gametes, subsequently resulting in the incidence of aneuploidy after fertilization and embryonic development defects. 17 In consistent with our present study, these former literature have revealed that the promotion of epigenetic modifications via the amelioration of mitochondrial dysfunctions significantly improved the development potentials of mammalian oocytes, 16,17,[64][65][66] further addressing the future applications of Se/CDs as dietary supplementation in mammalian IVM via the promotion of epigenetic modifications. However, the specific regulation mechanism related to the effect of Se/CDs' supplementation in the epigenetic modifications of ovine MII oocytes and the potential effect of Se/CDs' supplementation on the epigenetic modifications of ovine zygote and/or blastocyst need more detailed investigations.…”
Section: Dovepresssupporting
confidence: 91%
“…The epigenetic alterations induced by advanced maternal aging, mitochondrial dysfunctions, abnormal nutrition supply and abnormal expression levels of hormones trigger seriously meiotic defects of mammalian gametes, subsequently resulting in the incidence of aneuploidy after fertilization and embryonic development defects. 17 In consistent with our present study, these former literature have revealed that the promotion of epigenetic modifications via the amelioration of mitochondrial dysfunctions significantly improved the development potentials of mammalian oocytes, 16,17,[64][65][66] further addressing the future applications of Se/CDs as dietary supplementation in mammalian IVM via the promotion of epigenetic modifications. However, the specific regulation mechanism related to the effect of Se/CDs' supplementation in the epigenetic modifications of ovine MII oocytes and the potential effect of Se/CDs' supplementation on the epigenetic modifications of ovine zygote and/or blastocyst need more detailed investigations.…”
Section: Dovepresssupporting
confidence: 91%
“…Food & Function more ROS in oocytes because ROS is a byproduct of mitochondrial oxidative phosphorylation. [41][42][43] In this study, we found that the ROS concentration in diabetic oocytes was higher compared with the control. The excessive accumulation of ROS in diabetic oocytes is also demonstrated by other studies and the higher ROS level is deleterious to oocyte maturation, leading to DNA damage.…”
Section: Papersupporting
confidence: 51%
“…As expected, we observed that MV reduced ROS levels and increased the expression of antioxidant genes ( CAT and GPx1 ) in LPS-exposed oocytes. Excessive ROS accumulation originating from the external microenvironment and cellular metabolism may cause oxidative stress and further induce early apoptosis in oocytes ( Pandey et al, 2010 ; Jia et al, 2019 ; Zhang et al, 2020 ). Moreover, we found that MV reduced the occurrence of early apoptosis caused by LPS exposure.…”
Section: Discussionmentioning
confidence: 99%